(untitled) (Серія: Історія. Політологія, 2021)
У статті акцентується увага на проблемах врегулювання правового статусу механіків морських торговельних суден Приазов’я та Причорномор’я ХІХ - початку ХХ століть. Предметом детального вивчення стало «Высочайше утвержденное положение о механиках на мореходных судах торгового флота» 1903 р., що вперше законодавчо визнало наявність суднових механіків в структурі кадрового складу морських торговельних суден. Досліджується вплив нового законодавства на появу перших морських навчальних закладів, у яких здійснювалася підготовка кваліфікованих фахівців. This article reveals the problems of the personnel of the crews of sea-going merchant vessels of the Azov-Black Sea region. The unrestrained development of domestic and foreign trade in the conditions of a shortage of professional personnel of the merchant navy pushed the Russian Empire to the legal regulation of the competencies of ship mechanics in the early XX century. Until 1903, the legal status of mechanics in the Russian merchant navy was uncertain. Ship mechanics in the Trade Charter of 1893 were listed as members of the crew of free hire and were not part of the command staff. This created serious inconveniences both for ship captains, who found it difficult to cooperate with mechanics, and for mechanics who had no legal basis to manage their immediate subordinates (drivers and firemen). In addition, in the Russian Empire at that time there was no clear system of ship mechanics training for both cabotage and long-distance navigation due to the low level of population’s education, and insufficient attention from the state to the problems of the merchant navy. «Regulations about mechanics on ships of the merchant navy», approved in 1903 defined the state benefits to ship mechanics − deprivation from military service and enlistment in the command of the ship, provided an opportunity to obtain the rights of honorary citizen. It defined the requirements for those who aspired to obtain the positions of ship mechanics: reaching the age of majority, passing the tests of the qualification commission and the presence of a practical qualification. The regulation of the legal status of ship mechanics at the legislative level has influenced on the organization of their training in the Russian Empire. In 1901, a mechanical department for the training of ship mechanics was opened at the Odessa School of Merchant Shipping, for the first time in the Russian Empire. There were no educational institutions in which they could receive higher education in the early XX century. The appearance of the «Regulations on Mechanics on Merchant Navy Ships» in 1903 corrected the negative situation caused by the legal uncertainty of the rights and responsibilities of merchant navy mechanics. The provision raised the prestige of ship mechanics, who received officer’s rights and, at the same time, increased their salaries.